Additional diagnoses in children with cleft lip and palate up to five years of age. Issue 1 (28th February 2023) - Aspelin, Ellen; Cornefjord, Måns; Klintö, Kristina; Becker, Magnus
Abstract: Cleft lip and palate (CL/P) is the most common congenital craniofacial malformation and is often associated with additional diagnoses. The purpose of this study was to explore the cumulative five-year incidence of additional diagnoses for patients with cleft lip and palate. Further aims were, type of cleft and type of additional diagnose and to validate CLP registry data on additional diagnoses. Data from the CLP registry regarding children with CL/P in the Southern Health Care Region were retrieved and based on the registry, participants were selected. A review of medical records of participants born 2006–2016 was performed and data regarding participant characteristics and additional diagnoses were collected. Of the 250 participants included in the review of medical records, 90 participants (36%) had an additional diagnosis. Of the total number of identified additional diagnoses ( n  = 137), cardiovascular system (20.4%) and extremities and skeletal system (17.5%) were the most prevalent categories. The comparison between medical records and the CLP registry of all children showed a 14.4 percentage points higher incidence of additional diagnoses in the medical records. Roughly every third child received an additional diagnosis and diagnoses related to the cardiovascular system were the most frequent. This study also shows that additional diagnoses were under-reported in the CLP registry. Future research is necessary to strengthen associations of additional diagnoses to CL/P.